2024
DOI: 10.3390/ijms25021055
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cesarean Section Delivery on Intestinal Microbiota: Mechanisms, Consequences, and Perspectives—A Systematic Review

Francesco Inchingolo,
Alessio Danilo Inchingolo,
Irene Palumbo
et al.

Abstract: The relationship between cesarean section (CS) delivery and intestinal microbiota is increasingly studied. CS-born infants display distinct gut microbial compositions due to the absence of maternal birth canal microorganisms. These alterations potentially link to long-term health implications like immune-related disorders and allergies. This correlation underscores the intricate connection between birth mode and the establishment of diverse intestinal microbiota. A systematic literature review was conducted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 86 publications
0
2
0
1
Order By: Relevance
“…A diferencia de la investigación realizada por Czarnik y col. (Czarnik et al, 2024) Estos datos difieren de lo reportado con el estudio de Inchingolo y col (Inchingolo et al, 2024), se logró encontrar en mayor medida que ayuda a la modulación del metabolismo, la disfunción de la barrera en la inflamación metabólica. el microbiota intestinal puede influir en el almacenamiento de energía y la regulación del metabolismo de lípidos y carbohidratos, influyendo así en la acumulación de grasa corporal y la utilización de energía.…”
Section: Discussionunclassified
“…A diferencia de la investigación realizada por Czarnik y col. (Czarnik et al, 2024) Estos datos difieren de lo reportado con el estudio de Inchingolo y col (Inchingolo et al, 2024), se logró encontrar en mayor medida que ayuda a la modulación del metabolismo, la disfunción de la barrera en la inflamación metabólica. el microbiota intestinal puede influir en el almacenamiento de energía y la regulación del metabolismo de lípidos y carbohidratos, influyendo así en la acumulación de grasa corporal y la utilización de energía.…”
Section: Discussionunclassified
“…Using advanced sequencing techniques, fecal samples from 20 VLBW preemies were analyzed during both early and late feeding stages. The results highlighted that late stage feeding practices notably impacted both GM composition and oxidative stress levels [94]. Specifically, infants given fortified human milk or only F experienced higher oxidative stress compared to those receiving a mix of human milk (HM) and F. Diets influenced microbial diversity, and infants fed with F had fewer diverse microbes and increased levels of bacteria associated with oxidative stress.…”
Section: Gut Microbiota In F-fed Infantsmentioning
confidence: 98%
“…Cytokine production and migration affects bone and soft tissue metabolism by acting on NF kappa B ligand receptors (RANKL), osteoprotegerin (OPG), matrix metalloproteinases (MMPs) and tissue inhibitors of MMPs (TIMPs) [18,19]. Study findings revealed elevated concentrations of proinflammatory cytokines and markers of tissue and bone metabolism in gingival crevicular fluid (GCF) following the application of orthodontic forces [20,21]. Increased levels were observed after 4 h and persisted for up to 6 weeks.…”
Section: Introductionmentioning
confidence: 99%